Municipal waste recycling in big cities in Poland in the context of ecologisation - Lewandowska Aleksandra; Szymańska Daniela (Bulletin of Geography. Socio-Economic Series, 2019)
The goal of the paper is to evaluate and analyse changes in selective municipal collection, recycling level, and recovery, of waste. The article indicates the Polish legislation currently in force to systematise the organisation of waste management systems. It presents the participation of selective waste collection in the total municipal waste at the voivodeship scale, as well as changes in the number of individually segregated fractions (i.e. categories of waste segregation) of selectively collected waste in Poland. Moreover, the levels of waste recycling and recovery were analysed for the country’s ten largest cities, while also showing that the cities implement accepted goals of municipal waste recovery. On the example of Warsaw, the structure of collected waste was discussed and attention was paid to the problem of quality of collected waste, which results in it being sent to sorting facilities.